Batteries: 2D Monolayer MoS2–Carbon Interoverlapped Superstructure: Engineering Ideal Atomic Interface for Lithium Ion Storage (Adv. Mater. 24/2015). (17th June 2015) - Jiang, Hao; Ren, Dayong; Wang, Haifeng; Hu, Yanjie; Guo, Shaojun; Yuan, Haiyang; Hu, Peijun; Zhang, Ling; Li, Chunzhong
<x xml:space="preserve">Abstract</x> The synthesis of a 2D monolayer MoS2–carbon inter‐overlapped superstructure with an ideal MoS2/C atomic interface is demonstrated by H. Wang, S. Guo, C. Li, and co‐workers on page 3687. This superstructure shows very good performance for lithium‐ion batteries in terms of high reversible capacity, excellent rate capability, and outstanding cycling stability.